The last interview - Nevo, Eshkol 1971- (Other Press, 2020)
"From the internationally best-selling author of Three Floors Up, a literary page-turner that delves into the deepening cracks in a carefully constructed public persona. A writer tries to answer a set of interview questions sent to him by a website. At first, they stick to the standard fare: Did you always know you would be a writer? How autobiographical are your books? Have you written any stories you would never publish? Usually his answers in these situations are measured, calculated, cautious. But this time, when his heart is about to break and his life is about to crumble, he finds he cannot tell anything but the truth. The naked, funny, sad, scandalous, politically incorrect truth. Every question the writer tackles opens a door to a hidden room of his life. And each of his answers reveals that at the heart of every truth, there is a lie--and vice versa. Surprising, bold, intimate, and utterly engrossing, The Last Interview shows just how tenuous the lines are between work and life, love and hate, fact and fiction"--
"First published in Israel as Ha-Re'ayon Ha-Acharon by Kinneret Zmora-Bitan, Tel Aviv, in 2018." --Title page verso
Keywords: Authors / Fiction; Interviews / Fiction; Interpersonal relations / Fiction; Honesty / Fiction; Israel / Fiction; Authors, Israeli / Fiction; Authors and readers / Fiction; Midlife crisis / Fiction; FICTION / General; Midlife crisis; Authors, Israeli; Authors and readers; Authors; Honesty; Interpersonal relations; Interviews; Israel; Hebrew fiction / 20th century / Translations into English; Authorship; Domestic fiction; Fiction; Hebrew fiction